Multi-Resolution Rendering of Complex Animated Scenes - Wand, M.; Straßer, W. (Computer graphics forum, 2002)
We present a novel multi‐resolution point sample rendering algorithm for keyframe animations. The algorithm accepts triangle meshes of arbitrary topology as input which are animated by specifying different sets of vertices at keyframe positions. A multi‐resolution representation consisting of prefiltered point samples and triangles is built to represent the animated mesh at different levels of detail. We introduce a novel sampling and stratification algorithm to efficiently generate suitable point sample sets for moving triangle meshes. Experimental results demonstrate that the new data structure can be used to render highly complex keyframe animations like crowd scenes in real‐time. Categories and Subject Descriptors: I.3.3 [Computer Graphics]: Picture / Image Generation — Display Algorithms; I.3.6 [Computer Graphics]: Methodology and Techniques — Graphics data structures and data types; G.3 [Mathematics of Computing]: Probability and Statistics — Probabilistic algorithms.